MODELS USED TO ENHANCE THE QUALITY OF CLINICAL PRACTICE EVALUATION AMONG NURSING STUDENTS: A SYSTEMATIC REVIEW - Saputra, Muhamad Andika Sasmita; Sansuwito, Tukimin bin; Said, Faridah Mohd (Journal Of Nursing Science Research, 2024)
Background: Clinical practice evaluation in nursing education is crucial to ensuring students have the competencies for optimal nursing practice, aligning with WHO standards. However, data from NCSBN indicates a significant need for more effective and comprehensive evaluation models. Aim: This aims to do a systematic review to identify and analyse evaluation models used in nursing education to enhance the quality of clinical practice evaluation for students, as well as strengths and weaknesses. Methodology: This systematic review was conducted by searching electronic database sources through journal search engines such as Google Scholar, ProQuest, CINAHL, PubMed, and Science Direct. The inclusion criteria were open-access journals published within the last five years (2018-2023). A journal search used key terms "mobile phone application" and "nursing students". Analysing using PRISMA and Software computer for journal review. Results: 12 eligible journals were found relevant to the topic out of 5,727 journals. Journals that were not eligible were excluded based on exclusion criteria. Each journal provided systematic information regarding methods of evaluating nursing students' clinical practice. Conclusion: Implementing appropriate evaluation models is crucial to enhance the quality of clinical practice evaluation for nursing students. The selection of evaluation methods should also be tailored to the evaluation objectives, available resources, and clinical education context. Combining multiple methods is often used to obtain a holistic and accurate picture of students' performance.